Model Pengelolaan Zakat Untuk Kesehjateraan Umat - Raihan Eky Wahyudi; Qois Abdul Hadi; Aqilla Muhammad Ramadhan; Fauzi Ichsan Nurfadhli; Yayat Suharyat (Journal of Creative Student Research, 2023)
To maintain its status as an NGO-based social institution (non-governmental organization), quality management means that it is an important element of serving donors in general and mustahik in Empowered Village, especially as a result of which the process of collecting and disseminating synchronously using donor desires becomes effective. The management of Productive Zakat is carried out by the management and staff of the Indonesian Zakat house amil zakat institution. This research was conducted to thoroughly examine how Rumah Zakat Indonesia implements productive zakat management using the aim of improving the welfare of residents. Management of services in terms of collection, collection of donor data, collection of mustahik data, and increasing the standard of amyl to the point of distribution of zakat money in sync with institutional events. This study uses narrative qualitative methodology, using the author's primary research sense, meaning observation and interviews. As per the findings of the author's research,.